2013
DOI: 10.1007/978-1-4471-2428-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms of CADASIL

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy(CADASIL) is an inherited small-artery disease of mid-adulthood caused by mutations of the NOTCH3 gene. The disease is responsible for widespread white-matter Iesions associated with lacunar infarctions in varinus subcortical areas. The disease is responsible for migraine with aura and ischemic strokes, and is associated with various degrees of cognitive impairment and with mood disturbances. CADASIL is considered as a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 112 publications
(134 reference statements)
2
23
0
Order By: Relevance
“…2 Chabriat et al estimated that about 5 per cent of CADASIL patients suf fer from mania. 9 A study carried out by Valenti et al was considered to be the first to approach the topic of mood disorders in CADASIL with a systemic and structured assessment.…”
Section: Mood Disorders In Cadasilmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Chabriat et al estimated that about 5 per cent of CADASIL patients suf fer from mania. 9 A study carried out by Valenti et al was considered to be the first to approach the topic of mood disorders in CADASIL with a systemic and structured assessment.…”
Section: Mood Disorders In Cadasilmentioning
confidence: 99%
“…2 CADASIL occurs world wide and has been reported in many ethnic groups. The prevalence and disease burden are still undeter mined.…”
mentioning
confidence: 99%
“…Basal ganglia (BG), which receives inputs from thalamus and all cortical regions projecting back to the BG, mostly through BG-thalamo-cortical loops, seems to be involved in the sensory, emotional and cognitive integration of pain information between cortical and thalamic regions [11][12][13]. Brain imaging studies have shown decreased activation in the BG of migraineurs versus controls in the interictal period [14], increased activation (blood flow) during the ictal state and other non specific lesions [15,16]. More recently, significant differences in gray matter volume and function in response to pain have been observed interictally in the BG in migraineurs with higher frequency of attacks versus those with lower frequency [17].…”
Section: Introductionmentioning
confidence: 98%
“…With this, the age of onset and clinical presentations are multifactorious. Attacks of migraine with aura are the first clinical manifestation in 20-30% of patients (4). Mood disorders, anxiety disorders, psychotic disorders, adjustment disorders, behavioral disorders, personality disorders, drug addiction, and substance abuse are main psychiatric diagnoses in CADASIL patients (2).…”
mentioning
confidence: 99%
“…NOTCH 3 is expressed exclusively from smooth muscle cells located at arterial walls and mutations in the NOTCH 3 gene bring about degeneration of vascular smooth muscle cells and multiple small infarcts at the white matter and deep gray matter (4,11). How the NOTCH 3 gene engenders arteriopathy is unknown.…”
mentioning
confidence: 99%